Heat transfer in solid methyl alcohol - Korolyuk, O.A.; Krivchikov, A.I.; Sharapova, I.V.; Romantsova, O.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Thermal conductivity coefficient к(T) of two crystalline (orientationally-ordered and orientationally-disordered) phases of pure methanol (at temperatures from 2 K to Tm , Tm is the melting temperature), CH3OH + 6.6 % H2O glass from 2 K to Tg , Tg is the glass transition temperature and a supercooled liquid from Tg to 120 K has been measured under equilibrium vapor pressure. The dependence к(T) is described approximately as a sum of two contributions: кI(T) describing heat transport by acoustic phonons andкII(T) —by localized high-frequency excitations. The temperature dependences of the thermal conductivity of primary monoatomic alcohols CH3OH, C2H5OH, and C3H7OH in the glass state have been compared. Differentmechanisms of phonon scattering in the crystalline phases and glass have been analyzed. The кII(T) has been calculated within the Cahill–Pohl model. There is an anomaly of the thermal conductivity of the glass state near Tg (a smeared minimum in the к(T) — curve).